2019
DOI: 10.1002/uog.20348
|View full text |Cite
|
Sign up to set email alerts
|

Descent of fetal head during active pushing: secondary analysis of prospective cohort study investigating ultrasound examination before operative vaginal delivery

Abstract: Objectives To investigate if descent of the fetal head during active pushing is associated with duration of operative vaginal delivery, mode of delivery and neonatal outcome in nulliparous women with prolonged second stage of labor. Methods This was a prospective cohort study of nulliparous women with prolonged second stage of labor, conducted between November 2013 and July 2016 in five European countries. Fetal head descent was measured using transperineal ultrasound. Head–perineum distance (HPD) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
0
20
1
Order By: Relevance
“…reported that a change in the AoP > 15° predicted 73% of successful vaginal extractions in their cohort 18 . In a recent multicenter prospective study of women with prolonged second stage of labor, delta‐HPD was found to be inversely related to the duration of operative vaginal delivery, the risk of failure and the need of a subsequent Cesarean delivery 19 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…reported that a change in the AoP > 15° predicted 73% of successful vaginal extractions in their cohort 18 . In a recent multicenter prospective study of women with prolonged second stage of labor, delta‐HPD was found to be inversely related to the duration of operative vaginal delivery, the risk of failure and the need of a subsequent Cesarean delivery 19 .…”
Section: Discussionmentioning
confidence: 98%
“…Among the different ultrasound parameters that have been proposed for the evaluation of fetal head progression and prediction of delivery outcome, the AoP and HPD have gained popularity and are increasingly used in the management of abnormal labor progression [4][5][6][7][8][17][18][19][20][31][32][33][34][35][36] . On this basis, the recent ISUOG guideline has recommended their routine measurement in pregnancies with prolonged second stage of labor or before considering operative delivery 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kahrs et al 42,43 performed a multicenter study on the use of ultrasound before vacuum delivery. Recently, they performed a secondary analysis of their data assessing fetal head descent during active pushing and found that a lack of fetal descent during active pushing was associated with longer duration of operative vaginal delivery 44 . Interestingly, in some women, the fetal head was higher in the birth canal during maternal pushing than at rest.…”
Section: Discussionmentioning
confidence: 99%
“…LAM coactivation was recently found to be associated with longer second, active second stage of labor and with less engaged fetal head at term 15,17,22 . In a recent study conducted on women undergoing vacuum delivery, LAM coactivation was assumed to be the cause of lack of fetal head descent with maternal pushing 23 …”
Section: Discussionmentioning
confidence: 99%